Quantitative characterization of different occurrence states in medium maturity continental shale oil: a case study on eocene Shahejie formation shales, Qikou Sag, East China - Jiang, Wenya; Liu, Yuchen; Gao, Lijin; Liu, Guangdi; Feng, Jianyuan (Frontiers in Earth Science, 2025)
This study focused on the typical lithofacies of well QY12-1-1 in Qikou Sag, carried out geochemical experiments, multi-temperature pyrolysis experiments and stepwise solvent extraction of soluble organic matter analysis, and established quantitative evaluation techniques for different occurrence states of medium mature shale. Shale oil with different lithologic facies and different occurrence states in the core section of the Shahejie Formation in the Qikou Sag was quantitatively evaluated. An improved four-step pyrolysis scheme of 300°C, 375°C, 400°C, and 600°C was developed to experimentally analyze shale oil core samples. The results indicated that the free oil content of the Es3 shale in the Qikou Sag was 1.1–8.06 mg/g (average of 4.19 mg/g); the mobile oil content accounted for 54.72%. The adsorbed oil content was 2.2–3.73 mg/g, with an average of 2.05 mg/g. The mobile, heavy free, and adsorbed oil contents were high in the thin, medium, and thick-lamellar mixed shale, as well as in the thin and medium-laminated calcareous shale. The mobile, heavy free, and adsorbed oil contents in the thin-layered mixed shale exceeded that in the medium-laminated felsic shale, with the thin-laminated felsic and thick-layered mixed shales exhibiting the content values. The newly established characterization method of hydrocarbons with different occurrence states exhibited good correlation with the conventional pyrolysis methods and the distributed solvent extraction results. Therefore, the proposed method can be used to study the occurrence mechanism of shale oil and a rapid evaluation of shale oil content.